Responses to Low Doses of Ionizing Radiation in Biological Systems - Ludwig E. Feinendegen; Myron Pollycove; Charles A. Sondhaus (SAGE Publishing, 2004)
Biological tissues operate through cells that act together within signaling networks. These assure coordinated cell function in the face of constant exposure to an array of potentially toxic agents, externally from the environment and endogenously from metabolism. Living tissues are indeed complex adaptive systems. To examine tissue effects specific for low-dose radiation, (1) absorbed dose in tissue is replaced by the sum of the energies deposited by each track event, or hit, in a cell-equivalent tissue micromass (1 ng) in all micromasses exposed, that is, by the mean energy delivered by all microdose hits in the exposed micromasses, with cell dose expressing the total energy per micromass from multiple microdoses; and (2) tissue effects are related to cell damage and protective cellular responses per average microdose hit from a given radiation quality for all such hits in the exposed micromasses. The probability of immediate DNA damage per low-linear-energy-transfer (LET) average microdose hit is extremely small, increasing over a certain dose range in proportion to the number of hits. Delayed temporary adaptive protection (AP) involves (a) induced detoxification of reactive oxygen species, (b) enhanced rate of DNA repair, (c) induced removal of damaged cells by apoptosis followed by normal cell replacement and by cell differentiation, and (d) stimulated immune response, all with corresponding changes in gene expression. These AP categories may last from less than a day to weeks and be tested by cell responses against renewed irradiation. They operate physiologically against nonradiogenic, largely endogenous DNA damage, which occurs abundantly and continually. Background radiation damage caused by rare microdose hits per micromass is many orders of magnitude less frequent. Except for apoptosis, AP increasingly fails above about 200 mGy of low-LET radiation, corresponding to about 200 microdose hits per exposed micromass. This ratio appears to exceed approximately 1 per day for protracted exposure. The balance between damage and protection favors protection at low cell doses and damage at high cell doses. Bystander effects from high-dosed cells to nonirradiated neighboring cells appear to include both damage and protection. Regarding oncogenesis, a model based on the aforementioned dual response pattern at low doses and dose rates is consistant with the nonlinear reponse data and contradicts the linear no-threshold dose-risk hypothesis for radiation-induced cancer. Indeed, a dose-cancer risk function should include both linear and nonlinear terms.